Autonomous Harmonic Compensation in a Multi-Bus Micro-Grid Interfacing Converters through Fuzzy Logic Control - B. Venkata Prasanth, B. Mouli Chandra, S. Tara Kalyani, A. Prakash (Mathematical Statistician and Engineering Applications, 2023)
This paper proposes a novel approach to compensate buses voltage and current harmonics through distributed generation (DG) interfacing converter in a multi-bus micro-grid. The control approach of each individual DG unit was designed to use only feedback variables of the converter itself that can be measured locally. In the proposed approach, the adjacent bus voltage is indirectly derived from the measured DG converter output voltage, DG line current and line impedance. A closed-loop fuzzy controller is designed to achieve harmonics compensation. Therefore, the traditional harmonic measurement devices such as APF’s installed at the bus as well as the long distance communication between the bus and the DG converter are not required. The proposed approach can compensate the current harmonics, mitigate the buses voltage distortion and enable the customer devices to be operated in normal conditions within the multi-bus microgrid, and meanwhile relieve the burden of power quality regulator installed at the point of common coupling. Matlab simulations and experimental results are presented to show the operational effectiveness of the proposed approach.